Заселенность исскусственных гнездовий в дубравах Закарпатья - Симочко, M.Д. (Вестник зоологии, 1975)
18 species of hollow-nesting birds settle artificial nesting places in the Transcarpathian oak-groves. However Passer montanus L. dominates most often because of its great number and high ability to competition in struggle for nesting places. Placing nests at different height (0-4 m), sheltering them in undergrowth, in crowns of trees resulted in a considerable reduction of the number of nests in hollows occupied by sparrows and in an increase in the number of other birds nesting in lollows. Parus major L. and P. co- ruleus L. in particular.